Risk factors and outcomes in children with high-risk B-cell precursor and T-cell relapsed acute lymphoblastic leukaemia: combined analysis of ALLR3 and ALL-REZ BFM 2002 clinical trials. (July 2021) - Eckert, Cornelia; Parker, Catriona; Moorman, Anthony V.; Irving, Julie AE.; Kirschner-Schwabe, Renate; Groeneveld-Krentz, Stefanie; Révész, Tamas; Hoogerbrugge, Peter; Hancock, Jeremy; Sutton, Rosemary; Henze, Guenter; Chen-Santel, Christiane; et al.
Abstract: Aim: Outcomes of children with high-risk (HR) relapsed acute lymphoblastic leukaemia (ALL) (N = 393), recruited to ALLR3 and ALL-REZ BFM 2002 trials, were analysed. Minimal residual disease (MRD) was assessed after induction and at predetermined time points until haematopoietic stem cell transplantation (SCT). Methods: Genetic analyses included karyotype, copy-number alterations and mutation analyses. Ten-year survivals were analysed using Kaplan-Meier and Cox models for multivariable analyses. Results: Outcomes of patients were comparable in ALLR3 and ALL-REZ BFM 2002. The event-free survival of B-cell precursor (BCP) and T-cell ALL (T-ALL) was 22.6% and 26.2% ( P = 0 . 94), respectively, and the overall survival (OS) was 32.6% and 28.2% ( P = 0.11), respectively. Induction failures (38%) were associated with deletions of NR3C1 ( P = 0.002) and BTG1 ( P = 0 . 03) in BCP-ALL. The disease-free survival (DFS) and OS in patients with good vs poor MRD responses were 57.4% vs 22.6% ( P < 0.0001) and 57.8% vs 32.0% ( P = 0 . 0004), respectively. For BCP- and T-ALL, the post-SCT DFS and OS were 42.1% and 56.8% ( P = 0 . 26) and 51.6% and 55.4% ( P = 0 . 67), respectively. The cumulative incidences of post-SCT relapse for BCP- and T-ALL were 36.9% and 17.8% ( P = 0 . 012) and of death were 10.7% and 25.5% ( P = 0 . 013), respectively. Determinants of outcomes after SCT were acute graft versus host disease, pre-SCT MRD (≥10 −3 ), HR cytogenetics and TP53 alterations in BCP-ALL. Conclusion: Improvements in outcomes for HR ALL relapses require novel compounds in induction therapy to improve remission rates and immune targeted therapy after induction to maintain remission after SCT. Trial registration: ALLR3: NCT00967057 ; ALL REZ-BFM 2002: NCT00114348 Highlights: Paediatric high-risk relapsed B- and T-cell leukaemias have comparably poor outcomes. Determinants of induction failure in high-risk B-cell relapses were identified. Molecular good responders had better outcomes after stem cell transplantation. Benchmarks for evaluation of novel immune or targeted therapies were provided.